2018
DOI: 10.23937/2474-3674/1510047
|View full text |Cite
|
Sign up to set email alerts
|

Caring Critically Ill Patients in the General Wards in Tanzania: Experience of Nurses and Physicians

Abstract: Background: Studies in Tanzania have reported that many hospitals in the country have no intensive care unit (ICU) where critically ill patients could be managed thus critically ill patients are cared for with other non-critical patients. The aim of this study is to describe nurses and physicians' experience of caring critically ill patients in the general wards at the Regional hospital. Methods: A descriptive qualitative design was used. Purposeful sampling method was used to enroll 10 nurses and 5 physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Another reason for delaying tracheostomy in patients is to prevent the use of the procedure in patients with lesser injuries, who may be able to extubate successfully, and in those who have a rapidly progressive course of the disease and die early from their injuries. [13][14][15][16][17] In this study, there were differences in the length of stay in the intensive care unit for critically ill patients with mechanical ventilation who underwent early and late tracheostomy, where the length of stay was longer in the late tracheostomy group. This is consistent with studies that state that early tracheostomy is associated with a shorter average hospital stay (27 days) compared to standard tracheostomy (36 days) and late tracheostomy (48 days).…”
Section: Resultsmentioning
confidence: 89%
“…Another reason for delaying tracheostomy in patients is to prevent the use of the procedure in patients with lesser injuries, who may be able to extubate successfully, and in those who have a rapidly progressive course of the disease and die early from their injuries. [13][14][15][16][17] In this study, there were differences in the length of stay in the intensive care unit for critically ill patients with mechanical ventilation who underwent early and late tracheostomy, where the length of stay was longer in the late tracheostomy group. This is consistent with studies that state that early tracheostomy is associated with a shorter average hospital stay (27 days) compared to standard tracheostomy (36 days) and late tracheostomy (48 days).…”
Section: Resultsmentioning
confidence: 89%
“…The lack of human resource is fundamental and the consequences of the lack of skilled personnel was exposed during the various waves of the pandemic. As a result of shortages in trained specialists, there has been a strong reliance on generalist (non-specialist) and junior doctors, non-physician clinical officers and nurses to manage critically ill patients, under the supervision of the very few on call-specialists, as is the case in many other resource-limited setting [ 54 ]. We suggest that planning for the treatment of the critically ill in Kenya should prioritise the human resources required to provide the most effective forms of support to the widest group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians may also refer these patients to the intensive care unit (ICU) if they believe it will provide better monitoring and clinical management than the general ward. Staff issues such as nurse-to-patient ratios, skill, adequate training, and knowledge were identified by Mselle and Msengi as challenges in managing critically ill patients in the ward [ 21 ]. It was also reported that the general wards lacked specialised equipment to monitor and manage these patients, such as ventilators, infusion pumps, and basic oxygen delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases such as human immunodeficiency virus (HIV) and tuberculosis were more likely to be found in admitted patients compared to those rejected (21). Cardiovascular diseases such as hypertension and congestive cardiac failure (15), together with endocrine pathologies such as diabetes mellitus (8), were more common among the refused group.…”
Section: Secondary Outcomesmentioning
confidence: 99%